Mapeamento térmico urbano da cidade de Juazeiro do Norte, Ceará - Estevão, Gabriela de Souza (2022)
Society has fostered significant spatial changes, to the point of modifying the urban environment. The climate is one of the components that is subject to change and this is a cause for concern, since the conditions of urban environmental quality tend to decrease, in the face of disordered growth, such as socioeconomic disparities and environmental degradation. The mapping of climate information in the city is a resource that can be used to understand environmental issues and, above all, in decision-making for the planning of these cities. Thus, the objective of the research was to carry out the urban thermal mapping of the city of Juazeiro-CE. For that, four methodologies were Applied that allowed them to be distinct, being them looks at the urban climate (MCU), mobile transects, land cover index and Local Climate Zones (LCZs). In the MCU, the urban climate was considered, based on the energy balance of temperature, conditioned by the thermal load (heat gain and storage) and the heat storage potential (cooling). Building density, topography, permeable areas, soil cover, non-dense vegetation, roughness and slope orientation were mapped. Through the classification and weighting of the variables, it was possible to distribute and identify areas of the city according to their capacity to gain and store calories, as well as the areas with the greatest potential for temperature cooling. To validate the information from the MCU, 04 mobile transects were carried out in the years 2018 and 2020, contemplating paths in the north-east direction and measuring the air temperature of 114 points in total. The influence of the main types of cover/surfaces on the transects (concrete, ceramics, metallic cover, vegetation/drainage and exposed soil) was identified through the covering of the cover floor covering. Finally, the analysis of the urban morphology of the city and the analysis of the intensity and magnitude of the heat islands were carried out, using them as LCZs. The constructive standards are boosted by the high density of buildings, the use of traditional materials in urban equipment formed by waterproofing and watertight agglomerates, and the absence or results of evidence of open spaces and/drainage, especially in the densely populated neighborhoods of the city of Juazeiro. – EC reduction, were the main responsible for recording the highest temperatures (31.5°C), as well as the highest intensities and magnitudes (5.6°C) of heat islands.